Can We Use Hare's Psychopathy Model within Forensic and Non-Forensic Populations? An Empirical Investigation. Issue 2 (1st February 2018) - Debowska, Agata; Boduszek, Daniel; Dhingra, Katie; Sherretts, Nicole; Willmott, Dominic; DeLisi, Matt
ABSTRACT: Although psychopathy construct (Self-Report Psychopathy Scale–Short Form [SRP–SF]) was assessed among various samples, prior research did not investigate whether the model proposed by Hare and colleagues can be used to capture psychopathy scores derived from forensic and nonforensic populations. The main objective of the current study was to test dimensionality, construct validity, and factorial invariance of the SRP–SF within prison ( n = 730) and student ( n = 2, 506) samples. Our results indicate that the SRP–SF measure cannot be used in the same way within forensic and nonforensic samples, which may be due to the inclusion of criminal/antisocial traits as an integral part of psychopathy.